A dynamic model with vertical specialization, credit chains, and incomplete enforcement - Karsten Jeske (Federal Reserve Bank of Atlanta, 2002)
This paper sets up a model to account for differences in total factor productivity due to differences in enforcement of contracts. Vertical specialization generates the need for intra-period credit, because final goods producers cannot pay their intermediate goods suppliers before they produce their final good. The paper shows that if there are enforcement problems, the capital distribution is skewed in the sense that intermediate goods producers operate at lower capital levels and higher marginal products of capital than final goods producers. This wedge is created by the price for intermediate goods, which is lower in economies with bad enforcement. For this reason, the high-productivity firms in the intermediate goods sector have no incentive to grow and the low-productivity firms in the final goods sector, benefiting from low intermediate goods prices, have no incentive to shrink, which causes productivity to be lower in countries with bad enforcement.
Keywords: 330; Productivity; Contracts; Econometric models